A novel 8.57‐kb deletion of the upstream region of PRKAR1A in a family with Carney complex. Issue 3 (6th February 2022) - Ito, Shin; Hashimoto, Aya; Yamaguchi, Kazunori; Kawamura, Sadafumi; Myoen, Shingo; Ogawa, Maki; Sato, Ikuro; Minato, Takamichi; Miyabe, Shingo; Nakazato, Akira; Fujii, Keitaro; Mochizuki, Mai; et al.
Abstract: Carney complex (CNC) is a rare hereditary syndrome that involves endocrine dysfunction and the development of various types of tumors. Chromosome 2p16 and PRKAR1A on chromosome 17 are known susceptibility loci for CNC. Here we report a mother and son with CNC caused by an 8.57‐kb deletion involving the transcription start site and non‐coding exon 1 of PRKAR1A . The proband is a 28‐year‐old male with bilateral large‐cell calcified Sertoli cell testicular tumors and pituitary adenoma. Comprehensive genomic profiling for cancer mutations using Foundation One CDx failed to detect any mutations in PRKAR1A in DNA from the testicular tumor. Single‐nucleotide polymorphism array analysis of the proband's genomic DNA revealed a large deletion in the 5′ region of PRKAR1A . Genomic walking further delineated the region an 8.57‐kb deletion. A 1.68‐kb DNA fragment encompassed by the deleted region showed strong promoter activity in a NanoLuc luciferase reporter assay. The patient's mother, who is suffering from recurrent cardiac myxoma, a critical sign for CNC, carried an identical deletion. The 8.57‐kb deleted region is a novel lesion for CNC and will facilitate molecular diagnosis of the disease. Abstract : There is an inherited deletion of PRKAR1A gene that causes Carney complex. The deletion involves the promoter and non‐coding first exon of the PRKAR1A gene.